Earthquakes in the Vrancea zone and mantle seismic boundaries - Kendzera, A. V.; Ostrovnoy, A. N.; Tsvetkova, T. A. (Reports of the National Academy of Sciences of Ukraine, 2015)
2nd sort seismic boundaries are separated, by using the three-dimensional P-velocity model of the Europe mantle. These boundaries are related to changes in the velocity gradient ∂v(x,y,z)/∂z under the Vrancea area and adjacent territories. Statistics of the data for the Vrancea area earthquake foci presented in bulletins of the International Seismologic Centre are presented and interpreted.